2002
DOI: 10.1530/eje.0.1460001
|View full text |Cite
|
Sign up to set email alerts
|

Biology of the gonadotropin-releasing hormone system in gynecological cancers

Abstract: The expression of GnRH and its receptor as a part of an autocrine regulatory system of cell proliferation has been demonstrated in a number of human malignant tumors, including cancers of the breast, ovary and endometrium. Dose-dependent antiproliferative effects of GnRH agonists in cell lines derived from these cancers have been observed by various investigators. GnRH antagonists also have marked antiproliferative activity in most breast, ovarian and endometrial cancer cell lines tested, indicating that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
139
0
14

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(163 citation statements)
references
References 114 publications
9
139
0
14
Order By: Relevance
“…8,16 The number of patients in our study precludes speculation about association between clinical behavior and heterogeneous GnRH-R I and II expression but immunohistochemical detection of the receptors may identify tumor cells with an autocrine regulatory potential based on GnRH. 9 Interestingly, the five recurrent tumors in our series had high levels of GnRH-R I and II expression.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…8,16 The number of patients in our study precludes speculation about association between clinical behavior and heterogeneous GnRH-R I and II expression but immunohistochemical detection of the receptors may identify tumor cells with an autocrine regulatory potential based on GnRH. 9 Interestingly, the five recurrent tumors in our series had high levels of GnRH-R I and II expression.…”
Section: Discussionmentioning
confidence: 57%
“…For immunohistochemical analysis, representative 2-mm-thick sections of the endometrial stromal sarcomas were incubated with guinea-pig antisera to GnRH-R I (1:1000) and GNRH-R II (1:2000) after proteinase pretreatment. The antisera have been preciously characterized 8,9 and were generously provided by PD Dr Gundker, Department of Obstetrics and Gynecology, Georg-August University of Goettingen, Germany. Negative staining was recorded when 0-10% of tumor cells reacted with the antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…The activation of the peripheral GnRH receptor, which is coupled to the Gi protein in uterine leiomyosarcoma, ovarian and endometrial carcinomas, decreased intracellular cAMP levels leading to a down-regulation of gene transcription and antiproliferative effects in tumor cells [122] . Indeed, the repressive action of GnRH-I receptor on cell proliferation has been demonstrated in hormone-related tumors like prostate, breast, ovary and endometrium cancer [124] . GnRH and the cognate receptors were also involved in the stimulation of motility and invasion in ovarian cancer cells [125,126] , however several studies suggested a protective role elicited by GnRH analogues against gonadal damage during chemotherapy in diverse types of tumors [122] .…”
Section: Gpcrs Activated By Hormonesmentioning
confidence: 99%
“…The presence of GnRH receptors in breast cancer tissue [31] and the demonstration of antiproliferative actions of GnRH analogs in breast cancer cell lines [32,47,96] supported this interpretation. Antiproliferative effects of GnRH analogs and the expression of GnRH receptors have now been demonstrated in a number of cell lines of reproductive tract tumors, including prostate, uterine and ovarian cancers, and also in nonreproductive tract tumors [21,43,47,70,73,79]. In contrast to GnRH actions at the gonadotrope, which are mediated through the G αq protein, these antiproliferative and apoptotic effects on tumor cells are thought to be mediated via the G αi protein [42,54,81], focal adhesion complexes involving c-Src, and the JNK and P38 stress-activated kinases [42,54,70,73,81].…”
Section: Direct Inhibition Of Proliferation and Stimulation Of Apoptomentioning
confidence: 99%